Sensitive spectrophotometric assessment of carbofuran using dapsone as a new chromogenic reagent in formulations and environmental samples - Nagaraja, Padmarajaiah; Bhaskara, Besagarahally L. (Eclética Química, 2006)
A simple, sensitive and selective spectrophotometric method for the assessment of carbofuran in various formulations and in environmental water samples is described. The method is based on the coupling of hydrolyzed carbofuran with diazotized dapsone in alkaline medium at 0 – 4° C which gives orange red colored product having the absorption maximum at 480 nm. The product is stable for 48 h. Beer’s law is obeyed in the concentration range of 0.1 – 4.0 μg ml -1 . The molar absorptivity and Sandell’s Sensitivity are 5.0 x 10 4 L mol-1 cm -1 and 4.4 ng cm -2 respectively. The method is highly reproducible and is confirmed by RSD values (1.144 %). From the recovery studies it is found that this method is accurate and it can be successfully employed for the determination of carbofuran.